Kualitas minuman serbuk instan sereh (Cymbopogon citratus) dengan metode foam mat drying - Septiani Budi Ariska; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Lemongrass is still limited in use, namely more often for cooking ingredients. Lemongrass contains bioactive compounds that are beneficial to the body. This study aims to determine the quality of instant lemongrass powder drink with foam mat drying method. The method used in the study of instant lemongrass powder is the experimental design used was a factorial randomized block design (RAK) consisting of 2 factors, namely the concentration of maltodextrin (15%, 20%, and 30%) and the concentration of Tween80 (0.3% and 0 , 4%) so we get 6 treatment combinations. Each treatment was carried out 5 repetitions so that 30 trials were obtained. The tests included physicochemical (antioxidant, water content test, total dissolved solids, color test) and organoleptic tests (color, aroma, and taste). Data analysis was carried out using ANOVA. If significantly different, then proceed by using the Least Significant Difference test (BNT), organoleptic test using Friedman and to find the best treatment. The best results were found in the treatment of maltodextrin percentage 15% and tween 0.3% details of the results as follows: characteristics as follows color 3.04 (neutral / ordinary), aroma 3.6 (neutral / ordinary) and taste 4.12 (neutral / normal).